(untitled) (Archaeologia Adriatica, 2025)
In March 2022, archaeological trial excavations of the Neolithic site Pod Jarugom in Podgrađe were conducted. The aim of the excavations was to determine the stratigraphic and cultural relations at the site, its dating, and its potential for future systematic archaeological excavations. One trial trench with a surface area of 3 m2 was dug. The site was dated to the Middle Neolithic, that is to say the Danilo decorative style.